Incidental finding of gallbladder carcinoma detected during or after laparoscopic cholecystectomy. - Antonakis, P; Alexakis, N.; Mylonaki, D; Leandros, E; M Konstadoulakis, M; Zografos, G.; Androulakis, G. (Eur J Surg Oncol, 2003)
AIM: Carcinoma of the gallbladder is a rare neoplasm with a dismal prognosis. With the increase of cholecystectomies due to the wide acceptance of laparoscopic cholecystectomy, the incidental diagnosis of gallbladder carcinoma is more frequent. We report our experience with gallbladder cancer diagnosed during or after the performance of laparoscopic cholecystectomy. METHODS: We evaluated 11 patients with gallbladder cancer out of 5539 patients who underwent laparoscopic cholecystectomy. Patient clinical and demographic characteristics were reviewed. RESULTS: Intraoperatively in 297 patients there was the suspicion of adenocarcinoma and frozen sections were performed. In four of them the diagnosis of adenocarcinoma was confirmed. In two of them the procedure was converted to open with gallbladder liver bed resection and regional lymph node dissection while the other two were considered inoperable. Of the remaining 5242 patients, seven were diagnosed postoperatively at the pathologic examination. Of these, five patients refused to undergo a repeat operation. We did not observe port site metastasis in any of our patients. Survival was low and ranged from 3-14 months. CONCLUSION: Gallbladder cancer runs a short course, with a poor prognosis. The use of a meticulous laparoscopic technique seems to be important for the diagnosis and the avoidance of early complications of the disease.
Keywords: Adenocarcinoma; Aged; Cholecystectomy, Laparoscopic; Female; Gallbladder Neoplasms; Greece; Humans; Male; Middle Aged; Prognosis